PENCIPTAAN FILM DOKUMENTER “BADABUIH” DALAM ACARA ALEK NAGARI DI PADANG PARIAMAN - Gentha Nurha (Melayu Arts and Performance Journal, 2022)
The creation of the documentary film "Badabuih" is one of the films that aims to introduce the culture of the Padang Pariman region, especially the dabuih tradition in the nagari language. Documentary film is a type of film that deals with people, characters, events, or events. In this documentary "Badabuih" the author tries to see how the representation of the dabuih procession in Islamic culture in Padang Pariaman. In the process of creating the documentary film "Badabuih" the film is packaged into a series of plots in a linear manner with an approach to story and image elements with a chronological narrative structure. Listening further about the depiction or representation, many things are actually alluded to by other signs or symbols with a specific purpose. The events that occur in "Badabuih" then have a meaning between divine values and social values. These values then merge into a culture which then becomes entertainment. This film also explains how the view of dabuih that develops in the community as a means of giving thanks to Allah SWT..Keywords: Documentary Film; Badabuih; Representation; Padang PariamanABSTRAKPenciptaan film dokumenter “Badabuih” merupakan salah satu film yang bertujuan memperkenalkan kebudayaan daerah Padang Pariman khususnya tradisi dabuih dalam alek nagari. Film dokumenter merupakan jenis film yang berhubungan dengan orang-orang, tokoh, peristiwa, atau kejadian. Dalam film dokumenter “Badabuih” ini penulis mencoba melihat bagaimana representasi prosesi dabuih dalam budaya islam di Padang Pariaman. Pada proses penciptaan film dokumenter “Badabuih” film dikemas ke dalam rangkaian plot secara linier dengan pendekatan unsur cerita dan gambar dengan struktur penceritaan kronologis. Menyimak lebih jauh tentang penggambaran atau representasi, banyak hal yang sebenarnya dikiaskan dengan tanda atau simbol lain dengan maksud tertentu. Peristiwa yang terjadi dalam “Badabuih” kemudian memiliki makna antara nilai ketuhanan dan nilai sosial. Nilai-nilai tersebut kemudian menyatu menjadi suatu kebudayaan yang kemudian menjadi hiburan. Dalam film ini juga dijelaskan bagaiamana pandangan terhadap dabuih yang berkembang di tengah masyarakat sebagai salah satu sarana dalam melakukan syukur kepada Allah SWT.Kata Kunci : Film Dokumenter,Badabuih, Representasi, Padang Pariaman